Advances in Flavivirus Research - Michael R. Holbrook (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The flaviviruses are composed almost entirely of arthropod-borne viruses, a subset of which are responsible for millions of cases of human disease each year. Among these viruses are dengue virus-a scourge throughout the tropical regions of Asia and the Americas; yellow fever virus-the "original" hemorrhagic fever virus; and the recently emerged Zika virus. While the flaviviruses are related genetically, in their structure and in their replication processes, the dissimilarity of diseases caused by the flaviviruses is remarkable. In this Special Issue, primary research articles and reviews discuss topics ranging from broadly applicable questions of nuclear translocation of viral proteins to virus-specific envelope protein epitopes that may be associated with virus attenuation. Also included in this issue are articles discussing findings with less well known flaviviruses including pegivirus and Duck Tembusu virus. The latter provides a reminder that the flaviviruses not only impact humans, but other species as well.